Geographical vision of the prof. O. Vashchenko: projecting on contemporary - Oleh Shabliy; Myroslava Vlakh (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2018)
The contribution of the well-known Ukrainian economist-geographer, cartographer, organizer and long-time leader of the Department of Economic Geography of the Ivan Franko National University of Lviv O. Vashchenko on the theory, methodology and method of social geography, the main directions of the development of scientific ideas by the students and followers of the professor are determined. Prof. O. Vashchenko was one of the first in Ukrainian science to consider the subject and structure of economic ge-ography. O. Vashchenko is the first Ukrainian author who carried out the classification of economic-geographical science with the allocation of four classes of scientific disciplines: comprehensive synthetic, branch analytical, scientific and methodological, general education disciplines. The dominant features of the geographic worldview as a theory of cognition and social practice of geospatial development for prof. O. Vashchenko were specificity, geospatial differentiation and delimitation, systemicity and complexity, the use of the cartographic method of research. Interpretation of prof. O. Vashchenko subject of economic geography as the placement of productive forces predetermined the use of his cartographic method of research, and the system methodology – the appropriateness of atlas mapping. Prof. O. Vash-chenko is a worthy follower of the Galician cartographic tradition (S. Rudnyts'kyi, V. Kubiyovych), the founder of the Ukrainian Atlas Mapping in the postwar period (doctoral thesis "Atlas of the development of the economy of the western part of the Ukrainian SSR (from ancient times to the 70's of the twentieth century"), 1971). For the scientific worldview prof. O. Vaschenko is characterized by an organic combination of geography and historicism. Dominant signs of historicism of scientific views prof. O. Vaschenko: scientific and pedagogical activity in the field of geography history, geographic biography, periodization of the economy of the Western region of Ukraine (from ancient times to the 70's of the twentieth century), periodization of the formation and development of economic geography in Ukraine (1917–1977), the periodization of the research work of the Department of Economic Geography of Lviv University (1945–1965), as well as the transi-tion from the analysis of time dynamics to the analysis of the functioning of economic objects and their combinations. A general conclusion is drawn about the logical triad of scientific worldview prof. O. Vashchenko, formed by geography, his-toricism, economism, which are connected with cybernetic connections. Supplemented by ecological and humanitarian approaches, it determines the current progress of geographic science.